2022
DOI: 10.3389/fvets.2022.1043610
|View full text |Cite
|
Sign up to set email alerts
|

Brucella canis discospondylitis in 33 dogs

Abstract: ObjectiveTo describe the clinical and imaging findings of 33 dogs with Brucella canis discospondylitis (BDS).Animals33 client owned dogs from four veterinary specialty hospitals within Colorado and Arizona with at least one positive B. canis test and spinal diagnostic imaging.ProceduresRetrospective review of signalment, physical and neurological examination findings, laboratory results, B. canis serology, and diagnostic imaging of 33 dogs with BDS. All imaging was reviewed by a board-certified veterinary neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
1
8
2
Order By: Relevance
“…It is often recommended to use signalment, geographic location, and history to guide the decision to screen for brucellosis. Indeed sexually intact male dogs and dogs in the southeast or southwest United States are predisposed to Brucella canis ‐associated discospondylitis 16,17 . In contrast to these earlier reports, our study noted several sexually altered dogs with positive screening tests for discospondylitis with no apparent geographical predisposition.…”
Section: Discussioncontrasting
confidence: 94%
“…It is often recommended to use signalment, geographic location, and history to guide the decision to screen for brucellosis. Indeed sexually intact male dogs and dogs in the southeast or southwest United States are predisposed to Brucella canis ‐associated discospondylitis 16,17 . In contrast to these earlier reports, our study noted several sexually altered dogs with positive screening tests for discospondylitis with no apparent geographical predisposition.…”
Section: Discussioncontrasting
confidence: 94%
“…Our study revealed substantial delays in the diagnosis of B canis following the initial presentation of back or hip pain and gait abnormalities, and most of these dogs were < 5 years of age. A recent retrospective study 17 of B canis discospondylitis (BDS) in 33 dogs similarly revealed that dogs with BDS typically present at a young age and have a long duration of clinical signs leading up to their diagnosis. Taken together, these studies support the need to screen young dogs that present with signs of chronic back or hip pain, or recurring lameness, for B canis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other causes of discospondylitis, most dogs present with back pain, lameness and, less commonly, neurological deficits (Henderson and others 1974, Kornegay and Barber 1980, Thomas 2000). Interestingly, in a recent retrospective cohort study investigating B canis discospondylitis, most dogs were younger than five years of age and only 14 per cent (n=4/28) had a fever at presentation (Long and others 2022). Authors also noted marked chronicity to the signs, which perhaps contrasts with acute clinical signs associated with more common Gram‐negative infections (Van Hoof and others 2023).…”
Section: What Are the Clinical Signs In Dogs?mentioning
confidence: 99%